Cortical Amyloid beta in cognitively normal elderly adults is associated with decreased network efficiency within the cerebro-cerebellar system. - Stefanie eSteininger; Xinyang eLiu; Anton eGietl; Michael eWyss; Simon eSchreiner; Esmeralda eGruber; Valerie eTreyer; Valerie eTreyer; Andrea eKälin; Sandra eLeh-Seal; Alfred eBuck; Roger M Nitsch; et al. (Frontiers in Aging Neuroscience, 2014)
Deposition of cortical amyloid beta (Aβ) is a correlate of aging and a risk factor for Alzheimer Disease (AD). While several higher order cognitive processes involve functional interactions between cortex and cerebellum, this study aims to investigate effects of cortical Aβ deposition on coupling within the cerebro-cerebellar system. We included 15 healthy elderly subjects with normal cognitive performance as assessed by neuropsychological testing. Cortical Aβ was quantified using Pittsburgh Compound-B positron-emission-tomography (PiB-PET) late frame signals. Volumes of brain structures were assessed by applying an automated parcellation algorithm to three dimensional magnetization-prepared rapid gradient-echo T1-weighted images. Basal functional network activity within the cerebro-cerebellar system was assessed using blood-oxygen-level dependent (BOLD) resting state functional magnetic resonance imaging (fMRI) at the high field strength of 7 Tesla for measuring coupling between cerebellar seeds and cerebral gray matter. A bivariate regression approach was applied for identification of brain regions with significant effects of individual cortical Aβ load on coupling. Consistent with earlier reports, a significant degree of positive and negative coupling could be observed between cerebellar seeds and cerebral voxels. Significant positive effects of cortical Aβ load on cerebro-cerebellar coupling resulted for cerebral brain regions located in inferior temporal lobe, prefrontal cortex, hippocampus, parahippocampal gyrus and thalamus. Our findings indicate that brain amyloidosis in cognitively normal elderly subjects is associated with decreased network efficiency within the cerebro-cerebellar system. While the identified cerebral regions are consistent with established patterns of increased sensitivity for Aβ associated neurodegeneration, additional studies are needed to elucidate the relationship between dysfunction of the cerebro-cerebellar system and risk for AD.